Comprendre la loi ephebarchique d’Amphipolis - Χατζόπουλος, Μιλτιάδης (Tekmeria, 2017)
The author of the present article reviews the objections that have been raised to Calliope Lazaridou’s and his own interpretation of the recently published ephebarchical law from Amphipolis. To this end he exposes the overall plan of this legal document, devoting a special section to two of its articles which present a problem. He then examines the objections that have been raised a) against the identity of the two existing copies, b) against the common inspiration of the ephebarchical law of Amphipolis and the gymnasiarchical law of Beroia, and against the connection between the ephebarchical law and writings of classical authors on the education of the young. He concludes that the text engraved in 24/3 B.C. reproduces the provisions of the ephebarchical law promulgated under the Antigonids in the frst third of the second century B.C.